Bangkit Dari Keterpurukan: Pengembangan Usaha Mikro Melalui Pendampingan Legalitas Usaha Pada Masyarakat Desa Puntik Tengah - Sa'adiah Dwitiya Morty; Siti Zulaikha; Hekmah Nur Sari; Rizky Amalia; Muhammad Nordin; Muhammad Aqilla Shiddik; Siti Ramsiah; Apriana Kurnia Ningsih; Diyah Yasmina Utami (Prodi Sosiologi FISIP ULM, 2023)
Central Puntik Village is a village located in Mandastana District, Barito Kuala Regency, South Kalimantan Province. This village has problems in the economic sector, namely in the MSME sector, which needs further attention because most of them do not have business permits. MSMEs themselves have an important role in maintaining economic stability, so the high level of community participation causes their numbers to increase every year. MSME players still lack knowledge about business legality, so most do not have it. In order to support the sustainability and development of MSMEs in Central Puntik Village, the service team provides assistance to MSME actors to obtain legality which is marked with a Business Identification Number (NIB). This program was held on August 5 2023 with a series of activities starting from the opening by the MC, providing materials by the Garda Team, assistance with NIB registration by the service team, and the activity closed with lunch together. A form of assistance activity when registering for NIB registration, the service team accompanies the community to register an NIB account by filling out a registration form based on their KTP. As a result of this program, 30 MSMEs succeeded in having legal Business Permit Numbers (NIB). With the NIB, it is hoped that community businesses can develop in the future because their business products already have official permits. The service team was also assisted by several parties, namely by inviting resource persons and the Barito Kuala Transfumi Guard Team to assist in the process of making the NIB. The economic downturn due to crop failure has made some people try to get back up through additional income from MSMEs. What can be learned from this service is the importance of business awareness and motivation for the community regarding business licensing to support the smooth running of their MSMEs.